Meningitis 2012
DOI: 10.5772/29081
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Diagnosis of Meningitis

Abstract: Tuberculous meningitis (TBM), is common in those from countries where tuberculosis is common, and is also encountered in those with immune problems, such as AIDS. Despite advancement in vaccine development and chemoprophylaxis bacterial meningitis remains a major cause of death and neurological disabilities which can be prevented by rapid and accurate diagnosis with prompt treatment which is essential for good outcome (Carbonnelle, 2009). Viral meningitis is generally less severe and clears up without specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
0
11
2
1
Order By: Relevance
“…Bacterial meningitis leads to a predominance of neutrophils in CSF in about 80% -95% of bacterial meningitis cases [11]. The findings of this current study however indicated that only 21.3% of all culture positive cases had a neutrophil count greater than 5/mm 3 as shown in Table 5, which is regarded as a significant cut off value in the normal range of CSF neutrophil count [8].…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Bacterial meningitis leads to a predominance of neutrophils in CSF in about 80% -95% of bacterial meningitis cases [11]. The findings of this current study however indicated that only 21.3% of all culture positive cases had a neutrophil count greater than 5/mm 3 as shown in Table 5, which is regarded as a significant cut off value in the normal range of CSF neutrophil count [8].…”
Section: Discussioncontrasting
confidence: 68%
“…Gram stain yields positive results in 10% -15% of patients with bacterial meningitis, who test negative with culture results [11]. The current study found that Gram stain was only positive in 0.7% of the culture negative cases.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Los hallazgos identificados en el citoquímico de la PL como pleocitosis, con predominio de neutrófilos, hipoglucorraquia, e hiperproteinorraquia en conjunto con la identificación de la coloración Gram, fueron compatibles con meningitis bacteriana, con características plenas descritas en la literatura 13 . Se ha visto que en meningitis bacteriana los hemocultivos pueden identificar el Streptococcus pneumoniae en el 75% de los casos, y para el cultivo de LCR hasta en el 87% 13 . Nuestro paciente tuvo el mismo aislamiento microbiológico en ambos cultivos.…”
Section: Discussionunclassified